Counting Graph Homomorphisms - Borgs, Christian; Chayes, Jennifer; Lovasz, Laszlo; Sos, Vera T.; Vesztergombi, Katalin (Topics in Discrete Mathematics, 2006)
For two finite graphs G and H, let hom(G;H) denote the number of homomorphisms (adjacency-preserving mappings) from G to H. Counting homomorphisms between graphs has many interesting aspects.